PPARγ in Ischemia-Reperfusion Injury: Overview of the Biology and Therapy - Huang, Ruizhen; Zhang, Chiyu; Wang, Xing; Hu, Honglin (Frontiers in Pharmacology, 2021)
Ischemia-reperfusion injury(IRI),is a complex pathophysiological process which is often performed as blood circulation disorder caused by various causes(such as traumatic shock, surgery, organ transplantation, burn, thrombus, etc.), then the tissue appears severe metabolic disorder and the structure destruction when the ischemic tissue recovers the blood flow.Theoretically,IRI can occur in various tissues and organs, including: kidney, liver, myocardium, brain, etc. Although advances have been made in restoring tissues perfusion in ischemic areas, decreases in mortality and infarct size are still limited, attributing to IR injury.How to treat its severe consequences clinically remains a thorny issue.Peroxisome proliferator-activated receptors-γ(PPARγ) are members of a superfamily of nuclear transcription factors activated by agonists,is a promising therapeutic target for ameliorating IR injury.Thus, this review focuses on the role of PPARγ in IR injury. The protective effects of PPARγ, such as attenuating oxidative stress, inhibiting inflammatory responses, antagonizing apoptosis and are described and envisaging some therapeutic perspectives.